PERAN AKUNTAN DESA DALAM MENINGKATKAN TRANSPARANSI DAN AKUNTABILITAS DANA DESA ORO-ORO OMBO, KECAMATAN BATU - Indrihastuti, Poppy; Andika Putri, Sri; Muliati, Matildis (Unitri Press, 2025)
This study aims to assess how village accountants in Oro-Oro Ombo Village, Batu Regency, have improved accountability and transparency in village fund management. We collected data using descriptive qualitative techniques through documentation, interviews, and observations. The results of the study indicate that village accountants are critical in making clear and accurate financial reports, monitoring how money is spent, and teaching the village government and community about money management. Transparency is realized through the publication of budget information on social media and bulletin boards, while accountability is implemented through tiered reporting that involves various parties, including the community. This study stresses the importance of community participation in village financial management to prevent corruption and increase public trust in village governance. We expect the findings of this study to serve as a roadmap for enhancing village budget management.